Effects of 13-nle-motilin on the electrical and mechanical activity of the isolated perfused canine stomach and duodenum. Issue 5 (May 1976) - Green, W E; Ruppin, H; Wingate, D L; Domschke, W; Wünsch, D E; Demling, L; Ritchie, H D
Abstract : Synthetic 13-norleucine-motilin (13-nle-motilin), structural and biological analogue of the naturally-occurring duodenal polypeptide, motilin, is known to stimulate antral and duodenal motor activity in vitro, but delays gastric emptying in man. In this study the direct actions of the synthetic polypeptide on myoelectrical activity and intraluminal pressure have been studied in the isolated vascular-perfused canine stomach and duodenum. 13-nle-motilin increased intraluminal pressure in the pylorus and duodenum, and dose-response analysis showed the duodenum to be twice as sensitive as the pylorus to the polypeptide. Pressure changes in the antrum were small and not dose-related, but, whereas the basic electrical rhythm in the duodenum was not altered, slow wave frequency, rhythm, and propagation in the antrum were disturbed. Electronic analysis of the duodenal spike increase which accompanied pressure rises demonstrated correlations between increases in spikes, intraluminal pressure, and dose. These results show that the direct effect of the polypeptide on adjacent organs may explain the combination of increased motor activity with delayed gastric emptying as a consequence of disturbance in the co-ordination between antrum, pylorus, and duodenum.